Results of the multicentric management of infertility couples in Abidjan (Cote d’Ivoire) - Dia, Jean Marc; Sy, Telly; Bohoussou, Eric; Oyeladé, Mouhideen; Okon, Gerard; Guié, Privat; Anongba, Simplice (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The management of infertile couples has seen many advances characterized today by the different techniques of medically assisted procreation (MAP) that are increasingly practiced in the developed countries. The objective of present study is to describe our experience of multicentric management of infertile couples in our ivorian context. Methods: This is a retrospective and cohort study with descriptive purpose over 210 couples treated for infertility in the gynecology services of the University and Hospital Center of Treichville and a private clinic in Abidjan, from 1st February 2013 to 31st January 2017 (48 months). Results: The frequency of infertility was 14%, and the average age was 34.3 years for women and 43.2 years for men. The etiologies were found in 199 couples (94.8%), particularly in 136 women and 113 men. The main causes were uterine (58.1%), and hormonal (26.5%) in women and of infectious origin in men (79.7%). The majority of the patients (113 women and 97 men) received an etiologic treatment, dominated by myomectomia in women (67 patients) and targeted antiobitherapy in men (84.5%). Moreover 113 couples (53.8%) received a medically assisted procreation. After the management 110 couples (52.4%) got pregnant. Conclusions: The multicenter management has enabled infertile couples to have access to modern methods in their care.